2009
DOI: 10.1292/jvms.71.1079
|View full text |Cite
|
Sign up to set email alerts
|

Coprological Survey of Parasitic Infections in Pigs and Cattle in Slaughterhouse in Osaka, Japan

Abstract: ABSTRACT. A coprological survey was performed at a slaughterhouse in Osaka, Japan, from 2004 to 2007 on 129 pigs reared in 8 prefectures, and on 213 cattle reared in 21 prefectures. Eimeria spp., Trichuris suis, Ascaris suum and Metastrongylus spp. infections were found in 52 (40.3%), 32 (24.8%), 19 (14.7%) and 3 pigs (2.3%), respectively, while Eimeria spp., Capillaria bovis and Trichuris sp. infections were detected in 163 (76.5%), 15 (7.0%) and 8 cattle (3.8%), respectively. Our results suggest that environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
15
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 30 publications
3
15
0
3
Order By: Relevance
“…The result of Eimeria spp. infection is similar to [33] in Poland (58.5%), and [34] in Japan (40%) and highly differ from [35] in Ghana and [36] in China. The present result of Balantidium coli infection is differ from [21] in Korea (64.7%), [3] in Kenya (64%) and [37] in Danish (>57%).…”
Section: Faecal Sample Examination 311 Overall Prevalence Of Endopasupporting
confidence: 76%
“…The result of Eimeria spp. infection is similar to [33] in Poland (58.5%), and [34] in Japan (40%) and highly differ from [35] in Ghana and [36] in China. The present result of Balantidium coli infection is differ from [21] in Korea (64.7%), [3] in Kenya (64%) and [37] in Danish (>57%).…”
Section: Faecal Sample Examination 311 Overall Prevalence Of Endopasupporting
confidence: 76%
“…This severely impacts small-scale farmers in developing countries. Coprological examinations suggest that the percentages of pigs infected with T. suis is 25% in Japan (29), 32% in Kenya (31), 38% in Netherlands (11), and 17% in Uganda (32). Upon an animal's ingestion of infective T. suis eggs, the larvae penetrate the cecal and colonic mucosa in the pig intestine, where all subsequent stages of larval development take place.…”
mentioning
confidence: 99%
“…Humans with liver and lung lesions as well as cases and epidemics of eosinophilic pneumonia have been reported, and A. suum -specific antibodies were present in all cases [11-13]. In Japan and Turkey, 14.7% and 3.7% of pigs, respectively, were estimated to be infected with A. suum [7,14]. The prevalence of A. suum infection in the present study was 17.6%, which was lower than that in a previous report in Korea by Jang [2].…”
mentioning
confidence: 99%
“…Matsubayashi et al [14] recently reported that the prevalence of parasite infections in cattle were 76.5% for Eimeria spp., 7.0% for Capillaria bovis , and 3.8% for Trichuris spp. The prevalence of cryptosporidiosis in Korea was 8.9-98.2% in cattle and 9.9-47.7% in pigs [15].…”
mentioning
confidence: 99%